Neither economist nor historian - Eliot Roy Weintraub (Duke University, Center for the History of Political Economy (CHOPE), 2023)
Founded fifty years ago, the History of Economics Society served in its early years to support scholarship and teaching in the history of economic thought. But the decades long removal of history from economics departments and graduate programs has made the Society's mission increasingly irrelevant to the larger community of economists. In this partially autobiographical essay, the author argues that it is long past time for the Society to reassess its place among learned societies. Some suggestions for HES renewal appear in the paper's Appendix.
Keywords: A12; A14; A23; B00; B41; B50; 330; History of Economic Thought; economics graduate training; sociology of economics